«HIS WORKS BROKE THROUGH THE WALLS OF FOREIGN LITERATURES…»: GENESIS AND RECEPTION OF THE UKRAINIAN AND ENGLISH-LANGUAGE EDITIONS OF IVAN BAGRYANYI’S NOVEL «THE HUNTERS AND THE HUNTED» - Kurinna, Nataliia; Partyka, Vitaliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The aim of this study is to explore the genesis and reception of the Ukrainian and English-language editions of Ivan Bagryanyi’s novel The Hunters and the Hunted, published in the United States (St. Martin’s Press, New York, 1956), Canada (Burns and MacEachern, Toronto, 1954), and the United Kingdom (Macmillan, London, 1957). The analysis is situated within the ideological, philosophical, and aesthetic frameworks of 20th-century European and Ukrainian literature, particularly the postwar MUR (Artistic Ukrainian Movement) period. The study identifies the dominant features of Ivan Bagryanyi’s artistic vision, shaped by national worldview, existentialist philosophy, neo-romanticism, and the author’s literary anthropology. The article traces the genesis of the adventure novel The Hunters and the Hunted – from its initial conception in underground conditions to its first publication and subsequent wide international resonance. Special attention is given to the novel’s reception in the Western world, including reviews in leading English-language literary journals and media, as well as translations into other languages. Methodology. The analysis of the reception of Ivan Bagryanyi’s prose in the English-speaking world employs a combination of general scientific and philological methods, enabling a comprehensive understanding of both broad cultural and social processes and the specifics of literary textual analysis: the comparative-historical method facilitates the juxtaposition of Bagryanyi’s prose with that of George Orwell, Aleksandr Solzhenitsyn, Arthur Koestler, Milovan Djilas, and others within the context of global resistance to totalitarianism. Systems analysis views Bagryanyi’s works as elements of broader systems—diaspora culture, global anti-Soviet discourse, and Ukrainian national tradition—revealing interconnections among themes, ideologies, and reception. An interdisciplinary approach integrates insights from literary studies, cultural studies, translation theory, and history, enabling a nuanced understanding of the global cultural dialogue surrounding Bagryanyi’s legacy. The hermeneutic method is employed to interpret the deeper meanings, archetypes, and philosophical subtexts of the images (e.g., the stoic hero, the freedom fighter), as well as to analyze the characters’ worldviews and the author’s message. Comparative translation analysis allows for a comparison between the original Ukrainian texts and their English translations, exploring the extent to which Ukrainian specificity is preserved or adapted to fit the “Western” anti-Soviet rhetorical framework. Scientific novelty lies in the comprehensive analysis of The Hunters and the Hunted as a literary-documentary testimony of its time, combining the author’s autobiographical experience with elements of adventure, existential and anthropological reflection, and publicistic poetics. The article offers a systematic exploration of the novel’s genesis, the reception of its English-language translations, its international literary resonance, and the theoretical and practical challenges of rendering Bagryanyi’s text into English. Practical significance lies in the potential application of this research in teaching Ukrainian literary history, cultural studies, and history, as well as in translation practice, intercultural dialogue, and the global promotion of Ukrainian literature.